Effect of Inhaled Peppermint Aromatherapy on Chemotherapy-Induced Acute Nausea and Vomiting among Women with Breast Cancer in Gresik Regency - Istiroha Istiroha; Roihatul Zahroh; Qonitatin Wafiyah; Yuanita Syaiful (Indonesian Journal of Cancer, 2023)
Background: Chemotherapy-induced acute nausea and vomiting are commonly experienced by breast cancer patients. Therefore, this study aimed to determine the effect of inhaled peppermint aromatherapy on chemotherapy-induced acute nausea and vomiting among women with breast cancer.Methods: This pre-experimental study was conducted using a one-group pre-post-test design approach. The sample included 28 women with breast cancer undergoing chemotherapy at the Chemotherapy Unit of Semen Gresik Hospital, Gresik, Indonesia. Respondents were administered 0.25 cc of peppermint essential oil on a cotton ball and then inhaled for 10 minutes. Data were collected using Rhodes Index Nausea Vomiting & Retching (RINVR) and analyzed with a paired sample t-test.Results: The pre-test showed that the majority of respondents experienced a moderate level of nausea and vomiting. After the intervention, the post-test results indicated mild nausea and vomiting. The statistical analysis showed that peppermint aromatherapy significantly affected chemotherapy-induced acute nausea and vomiting with a p-value of 0.001 (α<0.05).Conclusions: There was a significant improvement in chemotherapy-induced acute nausea and vomiting after the administration of peppermint aromatherapy. Therefore, this intervention could be used as a non-pharmacological complementary therapy to reduce chemotherapyrelated nausea among breast cancer patients